A CASE REPORT ON WILSON'S DISEASE INDUCED LIVER CIRRHOSIS - Vincent, Bini; James, Aloysius; Tv, Syamaprasad; Reji, Reshma; Reghu, Remya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Wilsons disease is an inherited autosomal genetic abnormality genetic abnormality which results in impairment in cellular copper transport. Overtime this may leads to liver cirrhosis. The main focus of this case is to shows the importance of taking medical history. Here we discuss a case of 35 year old male diagnosed with Wilsons disease induced Liver cirrhosis and portal hypertension. He was physically very weak. Since the same genetic abnormality was the reason for the death of his sibling which was not considered while taking the medical history of this patient, this led to a late diagnosis of 4 years while the patient's condition became worst. Here in we report a case that provides an insight to medical professionals about taking proper medical history of patients. Key Words : Wilsons Disease, Liver Cirrhosis, Copper Deposit